Pengaruh Gaya Hidup Konsumtif dan Beauty Vlogger Sebagai Kelompok Referensi Terhadap Keputusan Pembelian Kosmetik (Studi pada Remaja Perempuan Pengguna Kosmetik Korea di Surabaya) - NOVIA FAADHILAH, FAUZ (Jurnal Ilmu Manajemen (JIM), 2018)
The last few years beauty industry in Indonesia invaded by products from the Korean. It raises a consumptive lifestyle for most teenage girls in Indonesia. The development of beauty vlogger in Indonesia also quite rapid. Poll survey results shows that respondents admitted, they often get information about cosmetic products through beauty vlogger and they said that influence of beauty vlogger makes them interested to buy new cosmetic products. This study used a quantitative research and non probability sampling technique with judmental sampling and snowball sampling. The number of samples in this study amounted to 100 respondents which is used likert scale as measurement in the form and using multiple linear regression analysis technique with application computer program SPSS for Windows 22. The results indicate that consumptive lifestyle partially have a positive effect on cosmetic purchase decisions. While beauty vlogger as a reference group in partial has no positive effect on cosmetic purchasing decisions of teenage girls as a Korean cosmetic consumer in Surabaya. Keywords: Beauty Vlogger, Consumptive Lifestyle, Reference Group, Purchase Decision.